The Importance of Phytoplankton Biomolecule Availability for Secondary Production - Peltomaa, Elina T.; Aalto, Sanni L.; Vuorio, Kristiina M.; Taipale, Sami J. (Frontiers in Ecology and Evolution, 2017)
The growth and reproduction of animals is affected by their access to resources. In aquatic ecosystems, the availability of essential biomolecules for filter-feeding zooplankton dependents greatly on phytoplankton. Here, we analyzed the biochemical composition, i.e., the fatty acid, sterol and amino acid profiles and concentrations as well as protein, carbon, nitrogen and phosphorus content of 17 phytoplankton monocultures representing the seven most abundant phytoplankton classes in boreal and sub-arctic lakes. To examine how the differences in the biochemical composition between phytoplankton classes affect their nutritional quality for consumers, we assessed the performance of Daphnia, on these diets. Furthermore, we defined the most important biomolecules regulating the somatic growth and reproduction of Daphnia, expecting that higher concentrations of certain biomolecules are needed for reproduction than for growth. Finally, we combined these results with phytoplankton field data from over 900 boreal and sub-arctic lakes in order to estimate whether the somatic growth of Daphnia is sterol-limited when the natural phytoplankton communities are cyanobacteria-dominated. Our analysis shows that Daphnia grows best with phytoplankton rich in sterols, ω-3 fatty acids, protein and amino acids. Their reproduction follows food sterol and ω-3 concentration as well as C:P-ratio being two times higher in Daphnia feeding on cryptophytes than any other diet. Interestingly, we found that a high dietary ω-6 fatty acid concentration decreases both somatic growth and reproduction of Daphnia. When combined with phytoplankton community composition field data, our results indicate that zooplankton is constantly limited by sterols in lakes dominated by cyanobacteria (≥ 40 % of total phytoplankton biomass), and that the absence of cryptophytes can severely hinder zooplankton production in nature.